Autophagy Reduces the Degradation and Promotes Membrane Localization of Occludin to Enhance the Intestinal Epithelial Tight Junction Barrier against Paracellular Macromolecule Flux. (11th October 2022) - Saha, Kushal; Subramenium Ganapathy, Ashwinkumar; Wang, Alexandra; Michael Morris, Nathan; Suchanec, Eric; Ding, Wei; Yochum, Gregory; Koltun, Walter; Nighot, Meghali; Ma, Thomas; Nighot, Prashant
Abstract: Background and Aims: Functional loss of the gut epithelium's paracellular tight junction [TJ] barrier and defective autophagy are factors potentiating inflammatory bowel disease [IBD]. Previously, we showed the role of autophagy in enhancing the intestinal TJ barrier via pore-forming claudin-2 degradation. How autophagy regulates the TJ barrier-forming proteins remains unknown. Here, we investigated the role of autophagy in the regulation of occludin, a principal TJ component involved in TJ barrier enhancement. Results: Autophagy induction using pharmacological activators and nutrient starvation increased total occludin levels in intestinal epithelial cells, mouse colonocytes and human colonoids. Autophagy induction enriched membrane occludin levels and reduced paracellular permeability of macromolecules. Autophagy-mediated TJ barrier enhancement was contingent on the presence of occludin as OCLN −/− nullified its TJ barrier-enhancing effect against macromolecular flux. Autophagy inhibited the constitutive degradation of occludin by preventing its caveolar endocytosis from the membrane and protected against inflammation-induced TJ barrier loss. Autophagy enhanced the phosphorylation of ERK-1/2 and inhibition of these kinases in Caco-2 cells and human colonic mucosa prevented the macromolecular barrier-enhancing effects of autophagy. In vivo, autophagy induction by rapamycin enhanced occludin levels in wild-type mouse intestines and protected against lipopolysaccharide- and tumour necrosis factor-α-induced TJ barrier loss. Disruption of autophagy with acute Atg7 knockout in adult mice decreased intestinal occludin levels, increasing baseline colonic TJ permeability and exacerbating the effect of experimental colitis. Conclusion: Our data suggest a novel role of autophagy in promoting the intestinal TJ barrier by increasing occludin levels in an ERK1/2 mitogen-activated protein kinase-dependent mechanism. Abstract : Inflammatory bowel disease [IBD] is associated with loss of the epithelial barrier-forming protein occludin. We show that autophagy, a degradative cell-survival mechanism, upregulates cellular occludin and enhances the epithelial tight junction [TJ] barrier against macromolecular flux and inflammation-induced barrier loss. Graphical Abstract: